Sequential growth factor releasing double cryogel system for enhanced bone regeneration. (October 2020) - Lee, Seunghun S.; Kim, Jung Hun; Jeong, Jiwoon; Kim, Seung Hyun L.; Koh, Rachel H.; Kim, Inseon; Bae, Sunghoon; Lee, Hoyon; Hwang, Nathaniel S.
Abstract: Bone regeneration is a complicated physiological process regulated by several growth factors. In particular, vascular endothelial growth factor (VEGF) and bone morphogenetic protein-4 (BMP-4) are regarded as key factors that induce bone regeneration by angiogenesis and osteogenesis. In this study, we developed a double cryogel system (DC) composed of gelatin/chitosan cryogel (GC) surrounded by gelatin/heparin cryogel (GH) for dual drug delivery with different release kinetics. VEGF was loaded in GH (outer layer of DC) for the initial release of VEGF to induce angiogenesis and provide blood supply in the defect area, while BMP-4 was loaded in GC (inner layer of DC) that leads to sustained release for continuous osteogenic induction. After analyzing characteristics of the double cryogel system such as porosity, degradation rate, swelling ratio, and mechanical properties, we evaluated release kinetics of VEGF (initial release) and BMP-4 (sustained-release) by ELISA. Then, the timely release of VEGF and BMP from DC synergistically induced in vitro osteogenic differentiation as confirmed by alkaline phosphatase staining, Alizarin Red S staining, and real-time PCR analysis. Finally, a critical-sized cranial defect model confirmed the enhanced bone regeneration as a result of dual release growth factor mechanisms. Graphical abstract: Overall schematic illustration of Double Cryogel system with dual growth factor release for bone regeneration. Image 1